Mengganti Kerugian Ekologi melalui Perspektif Pidana Denda - Nugroho, Fiska Maulidian (Pusat Kajian Hukum Perbankan Fakultas Hukum Universitas Jember, 2024)
The pattern of punishment through fines is not widely discussed, especially for law enforcement in the natural resources regime. Fines are always formulated together with other criminal threats, namely imprisonment because of its nature as a form of basic punishment. However, when the fine punishment is faced with acts that cause natural resources losses, the fine punishment has not been seen as a frightening threat or even more deterrent. Therefore, it is important to have a legal concept in a criminal perspective as a replacement for ecological damage. The purpose of this research is to find out the extent of criminal fines and its development, along with an in-depth analysis of criminal fines imposed on corporations to recover ecological losses in the future. This research method uses dogmatic legal research, which is based on literature review, policy, and current knowledge. The results of the discussion of this research include, fines are still not too favoured to deter criminals whose actions are charged with the consequences of damage to natural resources. Criminal fines also need to be reformulated through the basis and perspective of ecological losses, so that the content of the use of ecological losses can be the basis for higher and more optimal criminal fines.